2020
DOI: 10.1016/j.jhep.2019.10.028
|View full text |Cite
|
Sign up to set email alerts
|

A defect in endothelial autophagy occurs in patients with non-alcoholic steatohepatitis and promotes inflammation and fibrosis

Abstract: Deficient autophagy induces inflammation, features of endothelial-to-mesenchymal transition and apoptosis.Deficiency in endothelial autophagy promotes liver inflammation, liver cell apoptosis and liver perisinusoidal fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 58 publications
2
113
0
2
Order By: Relevance
“…These are key proteins for autophagic vesicle formation and lysosome maturation, and their deficit was found to suppress autophagic flux and to impair the autophagosome-lysosome fusion (Xu et al, 2013b). Moreover, autophagy could exert an anti-fibrogenic role since it promotes survival of hepatocytes and hepatocyte apoptosis is a central event in the fibrogenic process (Ni et al, 2014;Ruart et al, 2019;Hammoutene et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These are key proteins for autophagic vesicle formation and lysosome maturation, and their deficit was found to suppress autophagic flux and to impair the autophagosome-lysosome fusion (Xu et al, 2013b). Moreover, autophagy could exert an anti-fibrogenic role since it promotes survival of hepatocytes and hepatocyte apoptosis is a central event in the fibrogenic process (Ni et al, 2014;Ruart et al, 2019;Hammoutene et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with these findings, defective autophagy pathways in LSEC have been shown to occur in NASH patients compared with controls and steatotic patients. Autophagy deficiency was linked to liver inflammation, EndMT, apoptosis and perisinusoidal fibrosis in a mouse model of NAFLD, outcomes that were independent of metabolic risk factors such as body weight and plasma cholesterol ( Hammoutene et al, 2020 ). Furthermore, activation of autophagy with hypercholesterolaemia drug ezetimibe, via AMPK activation and nuclear translocation of transcription factor TFEB, ameliorated steatohepatitis by dampening inflammasome signalling in macrophages ( Kim et al, 2017 ).…”
Section: Lsec Pathophysiologymentioning
confidence: 99%
“…Aforementioned approaches which could maintain LSEC differentiation and function include restoration of their fenestrated phenotype, via BMP9 and GATA4 ( Geraud et al, 2017 ; Desroches-Castan et al, 2019 ), re-constitution of the VEGF/NO/sGC signalling pathway ( Tateya et al, 2011 ; Xie et al, 2012 ; Marrone et al, 2013 , 2015 ; Wang et al, 2013 ), and re-establishment of normal hedgehog signalling with hedgehog inhibitors such as tetramethylpyrazine ( Zhao et al, 2017 ). Furthermore, maintenance of autophagy pathways, which are known to be important for endothelial homeostasis and are defective in CLD patients ( Hammoutene et al, 2020 ), may offer an additional treatment strategy. Conservation of the LSEC phenotype and prevention of capillarisation may reduce the risk of progression from inflammation and fibrosis to irreversible cirrhosis and HCC.…”
Section: Targeting Lsec In Inflammation and Cancer Therapymentioning
confidence: 99%
“…Autophagy is a highly conserved physiological process controlling endothelial homeostasis in vascular beds [ 26 ]. Studies showed that autophagy defect results in endothelial dysfunction of patients with obesity and metabolic disorders, promoting the progression of ASCVD [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a highly conserved physiological process controlling endothelial homeostasis in vascular beds [ 26 ]. Studies showed that autophagy defect results in endothelial dysfunction of patients with obesity and metabolic disorders, promoting the progression of ASCVD [ 26 28 ]. Fasting is a classical and acknowledged method to regulate autophagy [ 29 31 ], which may probably make contributions to EPCs function.…”
Section: Introductionmentioning
confidence: 99%